Explaining sudden infant death with cardiac arrhythmias: Complete exon sequencing of nine cardiac arrhythmia genes in Dutch SIDS cases highlights new and known DNA variants. (May 2020) - Liebrechts-Akkerman, Germaine; Liu, Fan; van Marion, Ronald; Dinjens, Winand N.M.; Kayser, Manfred
Highlights: Previous genetic explanation of SIDS by cardiac arrhythmias was based on limited data. All exons from 9 cardiac arrhythmia genes (∼34, 000 Bp) sequenced in 142 Dutch SIDS cases. 40 novel and known DNA variants found in 60 (58.8 %) of the finally used 102 SIDS cases. 13 DNA variants with statistically significant SIDS association classified as likely pathogenic. Call for routine genetic SIDS screening for cardiac arrhythmias to save lives in affected families. Abstract: Previous studies suggested that Sudden Infant Death Syndrome (SIDS) can partially be genetically explained by cardiac arrhythmias; however, the number of individuals and populations investigated remain limited. We report the first SIDS study on cardiac arrhythmias genes from the Netherlands, a country with the lowest SIDS incidence likely due to parent education on awareness of environmental risk factors. By using targeted massively parallel sequencing (MPS) in 142 Dutch SIDS cases, we performed a complete exon screening of all 173 exons from 9 cardiac arrhythmias genes SCN5A, KCNQ1, KCNH2, KCNE1, KCNE2, CACNA1C, CAV3, ANK2 and KCNJ2 (∼34, 000 base pairs), that were selected to harbour previously established SIDS-associated DNA variants. Motivated by the poor DNA quality from the paraffin embedded material used, the application of a conservative sequencing quality control protocol resulted in 102 SIDS cases surviving quality control. Amongst the 102 SIDS cases, we identified a total of 40 DNA variants in 8 cardiac arrhythmia genes found in 60 (58.8 %) cases. Statistical analyses using ancestry-adjusted reference population data and multiple test correction revealed that 13 (32.5 %) of the identified DNA variants in 6 cardiac arrhythmia genes were significantly associated with SIDS, which were observed in 15 (14.7 %) SIDS cases. These 13, and another three, DNA variants were classified as likely pathogenic for cardiac arrhythmias using the American College of Medical Genetics guidelines for interpretation of sequence variants. The 16 likely pathogenic DNA variants were found in 16 (15.7 %) SIDS cases, including i) 3 novel DNA variants not recorded in public databases ii) 7 known DNA variants for which significant SIDS association established here was previously unknown, and iii) 6 known DNA variants for which LQTS association was reported previously. By having replicated previously reported SIDS-associated DNA variants located in cardiac arrhythmia genes and by having highlighting novel SIDS-associated DNA variants in such genes, our findings provide additional empirical evidence for the partial genetic explanation of SIDS by cardiac arrhythmias. On a wider note, our study outcome stresses the need for routine post-mortem genetic screening of assumed SIDS cases, particularly for cardiac arrhythmia genes. When put in practise, it will allow preventing further sudden deaths (not only in infants) in the affected families, thereby allowing forensic molecular autopsy not only to provide answers on the cause of death, but moreover to save lives.